Investigation of the Profitability of the Methods of Selecting for Predicting the Risk of Stock Price Fall in the supply chain of Companies Listed in Tehran Stock Exchange - Mohammadi, Hassan; Zarei Soudani, Alireza (International Journal of Supply Chain Management, 2019)
The aim of this study was to investigate the profitability of variable reduction methods for predicting the risk of the stock price drop of companies listed in Tehran Stock Exchange. To achieve this, the literature review was conducted and 24 primary variables were selected which were most frequently used in the literature and the required data for measuring them was available. The optimum variables were selected or extracted among the primary variables using variable selection methods (the correlation-based method and the relief method) and variable extraction methods (the factor analysis and the principal component analysis). Then, the risk of stock price fall for 101 companies listed in Tehran Stock Exchange was predicted for 2001-2015 using linear regression. In order to evaluate the performanceof the variable reduction methods, the evaluation criteria resulting from prediction using variables selected or extracted by these methods were compared with criteria resulting from prediction using all variables. Findings of the research indicated the profitability of variable reduction methods and significant differences between profitability levels of different methods. The results obtained from the investigation of the performance of different methods of prediction and variable reduction in the industry group indicated the effect of the type of industry on the prediction performance. Furthermore, the results of the prediction of returns during 2001-2015 showed that the performance of prediction was higher in some years and lower in some other years compared to the results of the collective investigation of the supply chain of companies in this period.